2003
DOI: 10.1111/j.1744-6570.2003.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Breach and Fulfillment of the Psychological Contract: A Comparison of Traditional and Expanded Views

Abstract: Breach and fulfillment in a psychological contract has traditionally been studied with approaches that are conceptually and methodologically limited. We compared predictions derived from the traditional view to predictions from an expanded view that maintains the distinction between promised and delivered inducements and examines their joint relationship with employee satisfaction. The traditional and expanded views were compared using longitudinal data and polynomial regression analysis. Results provided litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
307
6
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(372 citation statements)
references
References 93 publications
36
307
6
9
Order By: Relevance
“…Social exchange theory [26] predicts that organizations can promote individual positive attitudes and behaviors through providing employees with inducements. Our theoretical implication is consistent, but different, with the conclusion found by Lambert et al (2003) [50] and Shaw et al (2009) [66]. Lambert et al (2003) [50] found that organizations invested in employees through providing employees with vocational development, training opportunities, which could influence employees' attitudes and behaviors.…”
Section: Research Implicationssupporting
confidence: 78%
See 2 more Smart Citations
“…Social exchange theory [26] predicts that organizations can promote individual positive attitudes and behaviors through providing employees with inducements. Our theoretical implication is consistent, but different, with the conclusion found by Lambert et al (2003) [50] and Shaw et al (2009) [66]. Lambert et al (2003) [50] found that organizations invested in employees through providing employees with vocational development, training opportunities, which could influence employees' attitudes and behaviors.…”
Section: Research Implicationssupporting
confidence: 78%
“…Our theoretical implication is consistent, but different, with the conclusion found by Lambert et al (2003) [50] and Shaw et al (2009) [66]. Lambert et al (2003) [50] found that organizations invested in employees through providing employees with vocational development, training opportunities, which could influence employees' attitudes and behaviors. Shaw et al (2009) [66] found that EOR could lead to increasing employee performance and decrease quit intention.…”
Section: Research Implicationssupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, in line with earlier research, we distinguish between perceived obligations, which constitute the psychological contract, and the fulfilment of these obligations (Conway & Briner, 2005), and include two subscales to measure psychological contract breach (cf. Lambert et al, 2003;Robinson, 1996).…”
Section: Work and Stress 339mentioning
confidence: 99%
“…Based on the principles of social exchange theory (Cropanzano & Mitchell, 2005;Guest, 1998), psychological contract theory states that if employees perceive that their organization has not fulfilled its obligations, they will react with anger and frustration (Robinson & Morrison, 2000). More specifically, psychological contract breach is defined as the belief of an employee that the organization has failed to deliver its obligations (Lambert, Edwards, & Cable, 2003;Morrison & Robinson, 1997). Earlier research has revealed significant age differences in relations between psychological contract breach and work-related outcomes like job satisfaction, commitment and job turnover (Bal, De Lange, Jansen, & Van der Velde, 2008), and pointed to possible underlying age-related changes, such as a changing time perspective (perceptions of the individual's future), that may explain these effects (Bal, Jansen, Van der Velde, De Lange, & Rousseau, 2010).…”
Section: Introductionmentioning
confidence: 99%